2021
DOI: 10.1371/journal.pone.0258662
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the SEIPS model to guide hand hygiene interventions at a tertiary hospital in Ethiopia

Abstract: We aimed to apply the Systems Engineering Initiative for Patient Safety (SEIPS) model to increase effectiveness and sustainability of the World Health Organization’s (WHOs) hand hygiene (HH) guidelines within healthcare systems. Our cross-sectional, mixed-methods study took place at Jimma University Medical Center (JUMC), a tertiary care hospital in Jimma, Ethiopia, between November 2018 and August 2020 and consisted of three phases: baseline assessment, intervention, and follow-up assessment. We conducted que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…It was possible to analyze that all articles selected for this review addressed health professionals' practices in relation to HH during the pandemic. [15][16][17][18][19][20][21][22][23][24][25][26][27] Using Nola Pender's theoretical perspective, the studies showed some improvements of this preventive measure in health services, such as greater concern in preventing the spread of the virus and the execution of the correct technique in the five moments recommended by the WHO. However, overload.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was possible to analyze that all articles selected for this review addressed health professionals' practices in relation to HH during the pandemic. [15][16][17][18][19][20][21][22][23][24][25][26][27] Using Nola Pender's theoretical perspective, the studies showed some improvements of this preventive measure in health services, such as greater concern in preventing the spread of the virus and the execution of the correct technique in the five moments recommended by the WHO. However, overload.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was possible to verify that there are factors that weaken the HH process in hospitals, highlighting organizational barriers, such as insufficient supervision and minimal presence of an infection control team in care sectors. 21 It is worth noting that a difficult point still present in several hospitals is related to glove use as an option to replace HH. 17 They are considered one of the effective PPE in the context of biosecurity that guarantee protection during health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation